DUAL EDUCATION SYSTEM IN SMK MUHAMMADIYAH WANAREJA - Ningsih, Teti Kusuma; Santosa, Budi (Journal of Vocational Education Studies, 2019)
The purpose of this study was to determine the implementation of dual system education at SMK Muhammadiyah Wanareja, a vocational high school (VHS) in Central Java, Indonesia, starting from the preparation stage to the implementation and the obstacles faced and the solutions implemented. The method in this study used a descriptive qualitative technique with data collection, documentation, and observation. The data analysis technique uses the interactive techniques of Milles and Hubberman with the stages of data collection, data reduction, data presentation, and conclusion drawing. Test the validity and reliability of the data using the source triangulation technique. Respondents in this study were the vice principal of public relations affairs, teachers, students, and leaders or trainers from the industry. The results of the study show that the dual system education implemented is going well even though there are some obstacles in its implementation. Industrial work practice activities are carried out for the full six months and based on the results of competency tests carried out by the school after the industrial work practice activities. Data is obtained that students have competencies by following the expertise program and the competency grid determined by the school. Both institutions face obstacles in the implementation of dual system education. The obstacles faced by schools are the non-implementation of learning normative and adaptive subjects planned with online systems, the limited means of learning vocational and workforce practices. The obstacles faced by the industry are with single instructors and the number of participants in industrial work practices and implementation that are different from each school. Solutions implemented by schools related to normative and adaptive learning during the implementation of industrial work practices, schools conduct material enrichment for one month with a block system.